1993
DOI: 10.1038/ki.1993.343
|View full text |Cite|
|
Sign up to set email alerts
|

Tamm-Horsfall glycoprotein binds IgG with high affinity

Abstract: Tamm-Horsfall protein (THP), a monomeric glycoprotein (M(r) 80 to 100 kDa), is produced by the mammalian kidney's thick ascending limb of Henle cells and excreted into the urine. The function of THP is uncertain. Here we report that a high molecular weight contaminant in sheep THP (sTHP) preparations was identified as sheep IgG by its positive reaction with donkey anti-sheep IgG antibody and with protein G. To answer the question of whether sTHP and sheep IgG co-purified because of a physical interaction betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…These antibodies usually are of very low affinity [47] . Immunoglobulins also bind in an unspecific way to carbohydrates of uromodulin [48] . Therefore, it is likely that the described antiuromodulin antibodies in humans are not specific and are most likely an artifact.…”
Section: Uromodulin and Ckdmentioning
confidence: 99%
“…These antibodies usually are of very low affinity [47] . Immunoglobulins also bind in an unspecific way to carbohydrates of uromodulin [48] . Therefore, it is likely that the described antiuromodulin antibodies in humans are not specific and are most likely an artifact.…”
Section: Uromodulin and Ckdmentioning
confidence: 99%
“…A number of studies have suggested that UMOD plays a role in inflammation processes and modulation of immune system responses [3,[58][59][60][61][62][63][150][151][152][153][154][155][156][157][158][159] . This notion, however, comes mostly from in vitro studies or in vivo studies performed under artificial conditions, and their relevance for physiology and particularly for pathophysiology is debatable.…”
Section: Umod In Inflammation and Immunitymentioning
confidence: 99%
“…Specifically, uromodulin has been shown to induce pro-inflammatory cytokine release from human whole blood [8], to activate myeloid dendritic cells (DC) to acquire a fully mature DC phenotype [9], and to activate monocytes [8]. Precisely how uromodulin orchestrates these diverse immunological properties is unknown, however the protein has been shown to bind with high affinity to a number of immuno-proteins including the complement factors C1, C1q and C3 [10,11], IgG [12,13] and cytokines such as TNF alpha, IL-1 beta and IL-8 [14]. It is thought that these diverse but potent pro-inflammatory properties of uromodulin may signal tubular damage and repair [8,9].…”
Section: Introductionmentioning
confidence: 99%